Social Ethics and Local Literature: The Kabanti of Buton Traditions - Syahrul Ramadhan Hidayat; Nabilah Yusof; Taher Mohammad T. Jari (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
This journal examines the role of the kabanti tradition in projecting social ethics and local literacy in Buton, Southeast Sulawesi. Kabanti, a form of oral and written literature rich in Islamic and local cultural values, has become an important medium for the dissemination of Islamic teachings and the cultivation of social values within the Buton community. Despite facing challenges from globalization and digitization, the kabanti tradition persists as a vital part of Buton's cultural identity. This research employs an exploratory, sociological, and ethnographic approach to understand how kabanti maintains and strengthens the norms, values, and social identity of the Buton community. The results indicate that kabanti is not merely an oral and written tradition but also a social institution that influences the way of life and human interactions within the Buton community. Consequently, this research contributes to preserving and empowering local cultural heritage through the kabanti tradition.